Finite Element Simulation of Residual Stresses from Welding and High Frequency Hammer Peening - Gkatzogiannis, Stefanos (Berichte zum Stahl- und Leichtbau, 2022)
Research goal of the present monograph is the establishment of an efficient engineering approach, which will include straightforward but accurate simulation models, in order to estimate the residual stress fields of welded joints introduced during welding and their post-weld treatment with High Frequency Hammer Peening. The present subject lies on the intersection of structural engineering, material science and computational mechanics.